Um olhar direcionado às dificuldades De aprendizagem - Diniz, Maria dos Milagres Fernandes (2007)
With the intention to reflect on the difficulties of learning and the pedagogical practical that has been developed in the educational context, we carry through in this research, some reflexes regarding the learning difficulties, in special, the dyslexia. We opt, for an educational question, in presenting problematical of the phenomenon of the dyslexia, through of approaches of the difficulties of reading and writing that even so separate, the texts meet articulated and supplements. We carry through a case study, therefore we perceive between the childs taken care of in the NEDESP, our field of research, this pupil headed for the Aconhego school, that passing for one period of observation and assessment psychotherapist demonstrated to present dashes of dyslexia. Such in case that, we start to follow, to interview the mother and to analyze the educational material used by it in the school. Being able itself to conclude that the case study, it made possible I construct it of a critical, reflective and innovative work in the educational context, that certainly, to contribute for the deepening of studies on the dyslexia.